Sikap Muhammadiyah Terhadap Gerakan Islam Transnasional di Karanganyar - Alifian Choirudin Zain; Mutohharun Jinan (Jayapangus Press, 2026)
This study aims to analyze the phenomenon of the transnational Islamic movement and Muhammadiyah's response to its development in Indonesia. The research method used is a descriptive qualitative approach, and data collection techniques were conducted through literature studies, interviews, and documentation. Primary data were obtained through interviews with informants selected using a purposive sampling technique. The results of the study indicate that the development of the transnational Islamic movement in Indonesia is influenced by globalization, digital media, and ideological networks from the Middle East that enter through various channels. This phenomenon has given rise to various responses in society and has the potential to cause social friction if not understood contextually. In this regard, Muhammadiyah, as a moderate Islamic organization, responds through a progressive Islamic approach based on the principle of wasathiyah (religious moderation), emphasizing tolerance, inclusiveness, and strengthening religious and digital literacy. Thus, Muhammadiyah plays a role as a social agent in maintaining a balance between Islamic and Indonesian values ​​amidst the currents of globalization.